Model-Model Pembiayaan Pendidikan - Wirian, Oktrigana; Agustina, Nelly; Siahaan, Amiruddin (Educate: Jurnal Ilmu Pendidikan dan Pengajaran, 2022)
This article was written in order to construct the concept of education financing models. The type of writing in the article is qualitative research using library research with content analysis method as a data analysis tool. The description of the results of this article is that the ideal financing model in an area really depends on various conditions. It may be by choosing one or by combining two or more of the existing models. For Indonesia's condition, the financing model cannot be separated from central government subsidies, even though there is authority as mandated by the Regional Autonomy Law.